Exploring opportunities for integrating indigenous knowledge and practices into animal husbandry in Grade 10 Agricultural Science lessons - Siseho, Robert Simwanza (Rhodes University, Faculty of Education, Department of Education, 2019)
The performance of learners in Agricultural Science at secondary schools in the Omaheke region of Namibia is worrisome. For some years performance in the subject has been below the national average, even though the region is known for its agricultural activities. My assumption is that this could be compounded by the fact that even though the Namibian curriculum encourages teachers to integrate local or indigenous knowledge (IK) in their lessons, it is not clear how this should be executed. It is against this background that this study set out to explore opportunities for integrating indigenous animal husbandry knowledge and practices into the animal husbandry section of Namibian Grade 10 Agricultural Science lessons. This was a qualitative case study underpinned by the interpretive paradigm. The study first focused on finding out what practices and knowledge might be integrated into animal husbandry within Grade 10 Agricultural Science. Secondly, it aimed at finding strategies for integrating indigenous knowledge into Grade 10 Agricultural Science. Thirdly, using my experience of co-developing model lessons with two Grade 10 Agricultural Science teachers, it sought to identify what assistance teachers need to integrate IK. The fourth goal was to observe the lessons taught in order to find out how the two teachers mediated the lessons featuring IK. Data were collected using interviews, workshop discussions, observations (videotaped lessons) and reflections. The data were validated through member checking and triangulation via various techniques. I used Vygotsky's (1978) sociocultural theory and Wenger's (1998) community of practice as a composite lens to analyse my data. The findings showed that there is indigenous knowledge in animal husbandry of disease prevention and treatment, the feeding of livestock, castration, de-horning and parasite control. Strategies to integrate IK included inviting or visiting parents or farmers, using the learners' mother tongue and exploiting local resources. It emerged that teachers need help with teaching strategies, the development of worksheets, lesson planning and the use of technology. The mediation of the lessons included use of the chalkboard and a data projector, worksheets, the teacher assisting learners, and learners assisting one another. The study recommends that teachers integrate IK into their lessons to contextualize learning, increase learners' participation in class and enhance their understanding of science. It also recommends that curriculum developers make it clear how IK should be integrated and assessed. The study further recommends that institutions of higher education should train teachers on how to integrate IK in the curriculum.
Keywords: Agriculture -- Study and teaching -- Namibia; Ethnoscience -- Study and teaching -- Namibia; Ethnoscience -- Namibia